(untitled) (Vietnam Journal of Community Medicine, 2025)
Objectives: Investigate BK (Human polyomavirus) virus infection characteristics and their association with selected clinical and subclinical features in end-stage renal disease patients before kidney transplantation. Patients and methods: A cross-sectional study, including 80 kidney transplant patients and 80 healthy kidney donors at Military Hospital 103. Venous blood samples were collected and anticoagulated with ethylenediaminetetraacetic acid (EDTA). BK-IgG antibodies were detected using the ELISA kit. Results and discussions: In a cohort of 80 patients with end-stage chronic kidney disease, 21.3% (17/80) tested seropositive for BK-IgG, while 78.7% (63/80) were seronegative, showing no significant difference compared to the healthy control group. The prevalence of BK virus seropositivity was not significantly associated with age, gender, body mass index (BMI), etiology of renal failure, duration of dialysis, pre-transplant dialysis modality, or anemia status. Conclusion: Latent BK virus infection was detected at a significant prevalence using serological methods in end-stage chronic kidney disease patients before kidney transplantation.